En pandemis vetenskapliga verkligheter - Lundgren, Britta (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
The article concerns ethnological research about the Swine Flu-pandemic and the interdependence of and interference with medical disciplines. The insights from this multiplicity of reality-in-practice are important for society when facing future emerging infections.